Lessons for Europe from German monetary union - Marcel Fratzscher (DIW Economic Bulletin, 2015)
Precisely 25 years ago, on July 1, 1990, German monetary union came into force. On the same day, capital controls in Europe were abolished, creating the basis for European monetary union and the euro. These two historical events fundamentally changed Germany and the rest of Europe. Both German and European monetary union were and still are being heavily criticized and debated. Was the design of German monetary union wrong? Was it a mistake to adopt the euro? Particularly in terms of finding a solution to the current European crisis, it is important to understand what lessons Europe can take from German monetary union.
Keywords: E42; E58; F15; 330; German unification; European Currency Union; Greece